Economic Evaluation of Interventions for Screening of Dementia - Sanjib Saha; Ulf-G. Gerdtham; Håkan Toresson; Lennart Minthon; Johan Jarl (Lund University, School of Economics and Management, Department of Economics, 2018)
OBJECTIVE: The objective is to systematically review the literature on economic evaluations of screening interventions for early diagnosis of dementia disorders. METHODS: A systematic search of published economic evaluation studies in English was conducted using specified key words in relevant databased and websites. Data extracted included methods and empirical evidence (costs, effects, incremental cost-effectiveness ratio) and we assessed if the conclusions made in terms of cost-effectiveness were supported by the reported evidence. The included studies were also assessed for reporting quality using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. RESULTS: Fourteen studies were identified and broadly fell into two groups: screening without biomarkers and screening using biomarkers. There was a considerable heterogeneity in methodological approaches, target populations, study time frames, and perspectives as well as types of biomarkers used. The sensitivity and specificity of screening instruments are one of the important aspects in estimating the cost-effectiveness of the interventions. Cost-effectiveness of non-biomarker based interventions cannot be judged due to lack of information. The biomarkers based screening have the potential to be cost-effective but their effectiveness has to be established first. CONCLUSION: More economic evaluations studies as well as good quality effectiveness studies are required in screening strategies before these can be implemented in the clinical practice.
Keywords: H43; I10; I18; 330; Dementia; Screening; Early diagnostic; Economic evaluation